A hydrothermal coupling model for permafrost subgrade considering temperature gradient and its application - Jianqing Jia; Zeqing He; Victor O. Tenorio (Scientific Reports)
Abstract The thermodynamic properties of frozen soil depend on its temperature state and ice content. Additionally, the permeability coefficient significantly affects both the temperature distribution and water movement. In this study, the dynamic variation of soil permeability coefficient with temperature is considered, the permeability coefficient is defined as a piecewise function with temperature as independent variable, and the hydrothermal coupling equation is established. The freezing process of soil column is simulated by secondary development based on COMSOL software. The calculated outcomes align more closely with the experimental results when accounting for the temperature gradient. Notably, the calculation accuracy improves significantly for soil column heights between 0 and 3 cm and 8 to 15 cm, with a difference of only 0.005. On this basis, taking a road subgrade in a cold region as the background, the temperature boundary conditions of this subgrade are revised according to the conclusion of the 6th research report of IPCC, and the time-varying law and characteristics of its temperature field and moisture field are studied. The results show that the temperature gradient is larger within 2 m depth of the subgrade slope, and the temperature distribution is more uniform beyond 2 m, and there is permafrost. With the increase of subgrade depth, the moisture content of soil first increases, then decreases and finally tends to be stable, reaching the maximum at − 0.5 m, which is 13%.